2019
DOI: 10.1016/j.ajhg.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Length of Uninterrupted CAG, Independent of Polyglutamine Size, Results in Increased Somatic Instability, Hastening Onset of Huntington Disease

Abstract: Huntington disease (HD) is caused by a CAG repeat expansion in the huntingtin (HTT) gene. Although the length of this repeat is inversely correlated with age of onset (AOO), it does not fully explain the variability in AOO. We assessed the sequence downstream of the CAG repeat in HTT [reference: (CAG)n-CAA-CAG], since variants within this region have been previously described, but no study of AOO has been performed. These analyses identified a variant that results in complete loss of interrupting (LOI) adenine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
161
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(169 citation statements)
references
References 37 publications
7
161
1
Order By: Relevance
“…In other words, a loss of AGG interruption likely predisposes CGG repeat tracts to large-scale expansions (149,152). Generally, the stabilizing role of interruptions is common for expandable repeats and has been reported for GAA (153,154), CAG (38,128,129,(155)(156)(157)(158)(159)(160)(161)(162), CCTG (54,58,(163)(164)(165), and other repeats in somatic tissues, intergenerational transmission, and experimental systems.…”
Section: Relationship Between Repeat Size and Instabilitymentioning
confidence: 99%
“…In other words, a loss of AGG interruption likely predisposes CGG repeat tracts to large-scale expansions (149,152). Generally, the stabilizing role of interruptions is common for expandable repeats and has been reported for GAA (153,154), CAG (38,128,129,(155)(156)(157)(158)(159)(160)(161)(162), CCTG (54,58,(163)(164)(165), and other repeats in somatic tissues, intergenerational transmission, and experimental systems.…”
Section: Relationship Between Repeat Size and Instabilitymentioning
confidence: 99%
“…Recent studies have started to make progress in identifying modifier genetic variants, both for HD, 7–11 and other neurological disorders. 1214 For example, genetic variants in the interrupting sequence between the pathogenic CAG repeat and the polymorphic CCG repeat have been shown to influence age of onset of HD patients, and are particularly relevant for patients that carry reduced penetrance alleles.…”
Section: Introductionmentioning
confidence: 99%
“…1214 For example, genetic variants in the interrupting sequence between the pathogenic CAG repeat and the polymorphic CCG repeat have been shown to influence age of onset of HD patients, and are particularly relevant for patients that carry reduced penetrance alleles. 10, 11 Additionally, genome-wide association studies (GWAS) have identified trans -modifiers of clinical age of onset in HD, 7, 8, 10 and have highlighted the important role of DNA repair genes in modulating age of onset, potentially through altering the somatic instability of the CAG repeat.…”
Section: Introductionmentioning
confidence: 99%
“…Our generation of an isogenic series of C9-BAC mice with 800, 500 or 50 repeats has allowed us to directly demonstrate that longer repeat tracts result in earlier onset of behavioral abnormalities and decreased survival compared to shorter alleles. These results, combined with the somatic instability seen in patients, suggest that targeting DNA repair pathways may be a viable approach for mitigating disease in C9orf72 ALS/FTD (Jones et al, 2017, Wright et al, 2019. While reducing repeat tract length in our mice did reduce disease penetrance, several C9-50 mice did show ALS/FTD phenotypes.…”
Section: Discussionmentioning
confidence: 67%
“…While some expansion carriers remain asymptomatic into their 90s, the frequency of reduced penetrance is not yet clear because patients with symptoms are much more likely to be seen by a physician and genetically tested compared to asymptomatic mutation carriers , Murphy, Arthur et al, 2017. Repeat length and somatic repeat instability, which are known to contribute to Huntington disease and other repeat expansion disorders (Jones, Houlden et al, 2017, Lee, Wheeler et al, 2015, Wright, Collins et al, 2019, may contribute to the reduced disease penetrance of C9orf72 ALS/FTD, differences in age-of-onset and the wide-ranging clinical effects of the C9orf72 expansion mutation , Murphy et al, 2017. However, because of ascertainment bias, technical difficulties in measuring repeat length and somatic instability in patients, it is challenging to study the effects of repeat length as a modifier of C9orf72 ALS/FTD (Hsiung, DeJesus-Hernandez et al, 2012, Van Mossevelde, van der Zee et al, 2017a.…”
Section: Introductionmentioning
confidence: 99%